2017
DOI: 10.1037/com0000079
|View full text |Cite
|
Sign up to set email alerts
|

Do pigeons (Columba livia) use information about the absence of food appropriately? A further look into suboptimal choice.

Abstract: In the natural environment, when an animal encounters a stimulus that signals the absence of food-a 'bad-news' stimulus-it will most likely redirect its search to another patch or prey. Because the animal does not pay the opportunity cost of waiting in the presence of a bad-news stimulus, the properties of the stimulus (e.g., its duration and probability) may have little impact in the evolution of the decision processes deployed in these circumstances. Hence, in the laboratory, when animals are forced to exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 44 publications
2
27
3
Order By: Relevance
“…This was the case irrespective of condition order. These results are inconsistent with predictions of both the signal-value hypothesis (e.g., Stagner et al, 2012) and the recent models inspired by optimal foraging theory (Fortes et al, 2017;Vasconcelos et al, 2018). Probe trials with the S+ terminal-link stimuli of the Sig-Both condition revealed strong preference for the stimulus correlated with the higher frequency of reinforcement.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…This was the case irrespective of condition order. These results are inconsistent with predictions of both the signal-value hypothesis (e.g., Stagner et al, 2012) and the recent models inspired by optimal foraging theory (Fortes et al, 2017;Vasconcelos et al, 2018). Probe trials with the S+ terminal-link stimuli of the Sig-Both condition revealed strong preference for the stimulus correlated with the higher frequency of reinforcement.…”
Section: Discussioncontrasting
confidence: 92%
“…This was the case irrespective of condition order. These results are inconsistent with predictions of both the signal‐value hypothesis (e.g., Stagner et al, ) and the recent models inspired by optimal foraging theory (Fortes et al, ; Vasconcelos et al, ).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations